Physical and chemical investigation of water and sediment of the Keban Dam Lake, Turkey - Part 2: Distribution of radioactivity, heavy metals and major elements - Kulahci, F.; Dogru, M. (Springer, 2006)
Thirtynine surface water and 20 deep sediment samples were taken in different locations in Keban Dam Lake (Elazig. Turkey) to identify major sources and assess major elements. heavy metals. (CS)-C-137, Sr-90. total alpha- and total beta-distribution in 2003 and 2004 in four seasons each year. As a preliminary study heavy metal (Zn. Fe, Mn. Ni. Cu. Cr. and Co). major element (Mg, Ca. Na. K) and radioactivity con:centrations of (CS)-C-137. Sr-90, total-alpha and total-beta in the surface water and deep sediments were determined.
Keywords: Trace-Elements; Fish; Pollution; Victoria